INFRA-RED THERMOGRAPHY FOR DETECTING DROUGHT IN AGRICULTURAL CROPS AND SCHEDULING IRRIGATION - Petrović, Ivana; Marjanović, Milena; Ćosić, Marija; Savić, Slađana; Cvijanović, Gorica (Economics of Agriculture, 2016)
The use of thermal imaging is a fast growing and potentially important tool in various felds of agriculture. The technology visually identifed the rise of temperature in crop canopy which occurs as a result of drought and allows the precise scheduling of crop irrigation. The aim of presenting paper was to demonstrate the application of these techniques on potato plants and to point out on the necessity of irrigation for potato sustainable and economically justifed production.